2023
DOI: 10.1007/s00106-023-01323-9
|View full text |Cite
|
Sign up to set email alerts
|

Sprachverstehen im modulierten Störgeräusch bei bimodal versorgten CI-Tragenden

Abstract: Zusammenfassung Hintergrund Obwohl bei einer Versorgung mit Cochleaimplantaten (CI) ein gutes Sprachverstehen in Ruhe erreichbar ist, ist das Sprachverstehen im Störgeräusch gegenüber Normalhörenden (NH) stark beeinträchtigt. Bei einer bimodalen CI-Versorgung mit Hörgerät (HG) im Gegenohr beeinflusst das akustische Restgehör das Sprachverstehen im Störgeräusch. Fragestellung Ziel der Arbeit war es, das Sprachverstehen im Störgeräusch bei bimo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 21 publications
1
1
0
Order By: Relevance
“…Overall, speech could be discriminated at lower SNRs with icra5 noise than with olnoise. Since icra5 allows for listening into gaps in the noise signal ('gap listening' [30]), this finding is consistent with previous results using other speechmodulated noise signals [16,31,32]. For olnoise, the decrease from 18-30 to 71-80 years was smallest for the S 0 N 0,45,−45 condition (1.6 dB) and largest for the S 0 N 180,135,−135 condition (2.12 dB).…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Overall, speech could be discriminated at lower SNRs with icra5 noise than with olnoise. Since icra5 allows for listening into gaps in the noise signal ('gap listening' [30]), this finding is consistent with previous results using other speechmodulated noise signals [16,31,32]. For olnoise, the decrease from 18-30 to 71-80 years was smallest for the S 0 N 0,45,−45 condition (1.6 dB) and largest for the S 0 N 180,135,−135 condition (2.12 dB).…”
Section: Discussionsupporting
confidence: 91%
“…The SRT measured in fluctuating noise can be higher than that measured in stationary noise [15]. Weißgerber et al [16] conducted a study on amplitude-modulated Fastl noise and assessed the speech recognition of a group of bimodal cochlear implant users, comparing their results to age-matched hearing aid users, individuals without subjective hearing loss, and a young normal hearing control group. The researchers observed that speech recognition in modulated noise was more considerably impacted than in continuous noise with an increase in hearing loss.…”
Section: Introductionmentioning
confidence: 99%